Pengaruh Kemandirian dan Minat Belajar Terhadap Prestasi Belajar Ilmu Pengetahuan Sosial - Arief Muda Kusuma (Universitas Indraprasta PGRI, 2021)
The research aims to analyze and test the truth of hypotheses regarding the influence of learning independence and interest in the learning achievement of Private Junior High School students in South Jakarta. The research hypotheses tested include: There is an influence of independence and interest in learning together on the learning achievement of Private Junior High School Students in South Jakarta. There is an influence of independence on the learning achievement of Private Junior High School Students in South Jakarta. There is an influence of learning interest on the learning achievement of Social Sciences Private Junior High School Students in South Jakarta. The research was conducted by survey method. Analyzed using multiple regression analysis. The results of hypothesis testing came to the following conclusion: 1) There is a significant influence of independence and interest in learning together on the learning achievement of Private Junior High School Students in South Jakarta. This can be proven by the value of Sig.= 0.000 < 0.05 and Fh = 97,679. 2) There is an insignificant influence of independence on the learning achievement of Private Junior High School Students in South Jakarta. This can be proven by the value of Sig.= 0.727 > 0.05 and th = 0.351. 3) There is a significant influence of learning interest in learning achievements of Private Junior High School Students in South Jakarta. This can be proven by the value of Sig.= 0.000 < 0.05 and th = 8,680.